2021
DOI: 10.1111/faf.12601
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of freshwater fish assemblages, their background and methods of quantifications—A synthesis

Abstract: The temporal dynamics of biotic communities have been widely examined by ecologists. However, systematic reviews on how habitat features, sampling and data evaluation influence temporal patterns are rather sporadic. Here, we reviewed 307 peer‐reviewed scientific articles to characterize the methods and the approaches, as well as to identify the knowledge gaps in the assessment of the temporal dynamics of freshwater fish assemblages with special regard to their stability patterns. The number of publications inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 234 publications
(225 reference statements)
0
5
0
2
Order By: Relevance
“…Despite the advantages of eDNA, in detecting taxa, its limitations in areas like streams and rivers should also be considered while designing any study, like eDNA dilution and dispersion, environmental factors influencing eDNA degradation, quantitative challenges in relating eDNA concentration to actual species abundance and accumulation of eDNA from upstream sources leading to false detection in downstream sites. These limitations emphasize the importance of a mixed approach, recognizing the strengths of both traditional and eDNA‐based methods and mitigating the limitations associated with each method (Czeglédi, Sály, et al., 2021; Czeglédi, Specziár, et al., 2021; Eggleton et al., 2010). A study by Jo and Yamanaka (2022) notes that most eDNA particles can travel up to 2 km downstream under normal hydrogeographic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of eDNA, in detecting taxa, its limitations in areas like streams and rivers should also be considered while designing any study, like eDNA dilution and dispersion, environmental factors influencing eDNA degradation, quantitative challenges in relating eDNA concentration to actual species abundance and accumulation of eDNA from upstream sources leading to false detection in downstream sites. These limitations emphasize the importance of a mixed approach, recognizing the strengths of both traditional and eDNA‐based methods and mitigating the limitations associated with each method (Czeglédi, Sály, et al., 2021; Czeglédi, Specziár, et al., 2021; Eggleton et al., 2010). A study by Jo and Yamanaka (2022) notes that most eDNA particles can travel up to 2 km downstream under normal hydrogeographic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We examined how temporal change in fish assemblage composition and hydrologybeta diversity relationships varied among rivers across two spatial extents -the extent of river reaches (<100 km) and the extent of river systems (>1000 km). Our analyses revealed inter-annual changes in fish beta diversity and hydrological-beta diversity relationships differ when assemblages were assessed across short portions of rivers ('reaches') versus across broader extents spanning entire river 'systems' ( Assessing temporal change in the composition of ecological assemblages is fundamental to interpreting trends in biodiversity and biodiversity responses to anthropogenic environmental change (Czeglédi et al, 2022;McGill et al, 2015). We found that patterns of inter-annual change in fish assemblage composition were inconsistent when compared at the extent of reaches versus broader river systems.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing temporal change in the composition of ecological assemblages is fundamental to interpreting trends in biodiversity and biodiversity responses to anthropogenic environmental change (Czeglédi et al, 2022; McGill et al, 2015). We found that patterns of inter‐annual change in fish assemblage composition were inconsistent when compared at the extent of reaches versus broader river systems.…”
Section: Discussionmentioning
confidence: 99%
“…Complex interactions further act to alter and destroy aquatic environments (e.g., river temperature, nutrient load, chemical concentration, water volume, and flow adjustment) and their biota, especially sensitive species [10][11][12]. As the interactions between river temperatures and aquatic activities, a little fluctuation in ambient temperature and toxicant concentration can severely impact the physiological response of fish.…”
Section: Introductionmentioning
confidence: 99%